THE INFLUENCE OF PEOPLE, PROCESS, PHYSICAL EVIDENCE ON PATIENT SATISFACTION IN A HOSPITAL CUT MEUTIA NORTH ACEH - Fitrah Rahmadhani; Sapna Biby; Heriyana; Nurainun (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Patient satisfaction is a common phenomenon that poses challenges in marketing. In 2022, every year there will be ups and downs in the number of inpatients at Cut Meutia Hospital. Where in 2022 alone, the number of inpatients will only be 11,876 patients. This number decreased slightly from the previous year's number, namely 14,827 patients for 2021 at the Cut Meutia Hospital, North Aceh. The decrease in the number of patient visits is a problem that must be considered by hospital management. The decreasing number of patient visits will affect hospital income/income. Another impact is that operational activities are disrupted. A decrease in patient visits indicates that patients are disloyal which can be caused by patient dissatisfaction with the services provided by the hospital. The aim of this research is to determine the influence of people, process, physical evidence on patient satisfaction in receiving treatment at Cut Meutia Hospital, North Aceh. The population in this study were patients at Cut Meutia Hospital, North Aceh and the sample in this study was 96 respondents selected using the accidental sampling method. The data analysis method used is multiple linear regression analysis. The results of this research show that people, process, physical evidence have a significant effect on patient satisfaction in receiving treatment at Cut Meutia Hospital, North Aceh.